2023
DOI: 10.1038/s41612-023-00544-7
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transformation of wildfire emissions to harmful background aerosol

Christina N. Vasilakopoulou,
Angeliki Matrali,
Ksakousti Skyllakou
et al.

Abstract: Wildfires are a significant source of organic aerosol during summer, with major impacts on air quality and climate. However, studies in Europe suggest a surprisingly low (less than 10%) contribution of biomass burning organic aerosol to average summertime fine particulate matter levels. In this study we combine field measurements and atmospheric chemical transport modeling, to demonstrate that the contribution of wildfires to fine particle levels in Europe during summer is seriously underestimated. Our work su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…1 where it increased by 0.04. During the experiments, when SOA was formed, PMF analysis (Paatero and Tapper, 1994) in the ambient revealed that the less oxidized organic aerosol factor (LO-OOA) was dominating while the more oxidized factor (MO-OOA) had low levels at the time (Vasilakopoulou et al, 2023). This indicates that the corresponding air masses were less aged.…”
Section: Results Of Other Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 where it increased by 0.04. During the experiments, when SOA was formed, PMF analysis (Paatero and Tapper, 1994) in the ambient revealed that the less oxidized organic aerosol factor (LO-OOA) was dominating while the more oxidized factor (MO-OOA) had low levels at the time (Vasilakopoulou et al, 2023). This indicates that the corresponding air masses were less aged.…”
Section: Results Of Other Experimentsmentioning
confidence: 99%
“…transported over long distances and biogenic emissions in the Eastern Mediterranean. It combined both chamber experiments and ambient measurements (Vasilakopoulou et al, 2023;Matrali et al, 2024). Situated at an elevation of 1300 meters above sea level, the site was positioned at the chalet atop the Pertouli ski resort (39° 32'44"N 21° 29'55"E), in the middle of a sprucefir forest.…”
Section: Spruce-22 Campaignmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the photochemically-aged features of the smoke reaching NYC, our real-time trace metal measurements were key to identifying and constraining wildfire influences, especially for lowintensity or long-range transported aged smoke episodes (Vasilakopoulou et al, 2023). Potassium is often one of the most abundant metals in biomass burning aerosol emissions (Reid et al, 2005),…”
Section: Introductionmentioning
confidence: 99%